Management Whitepaper: An Audience Interpretation of Professional Athlete Self-Presentation on Twitter - Katie Lebel; Karen Danylchuk (Journal of Applied Sports Management, 2014)
Research Problem The purpose of this paper is to explore audience interest in the self-presentation strategies of professional athletes on Twitter and ascertain the self-presentation strategies that are perceived as most important to an athlete’s digital image. This research is important because it indicates not only what Twitter users are interested in, but also what types of content potential non-users might be enticed by. The study offers evidence of broad Twitter awareness among a varied demographic of sport consumers and suggests that sport fans may not be as interested in the personal details of their favourite athletes’ lives as previously proposed. The research also highlights an apparent disconnect between how athletes are electing to present themselves on Twitter and what audiences report being most interested in. This article would be useful to media and communication practitioners, particularly those involved with the development of social media strategy or athlete branding. Other sport managers attempting to keep up with the rapid growth of social media and its impact on their business may also find this article useful.